Ischemic Stroke among Young Adults Visiting a Referral Hospital in Ethiopia: The Impact of Rheumatic Heart Disease (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: stroke; rheumatic heart disease; atrial fibrillation; young adults